Development of Anti-inflammatory Probiotic Limosilactobacillus reuteri EFEL6901 as Kimchi Starter: in vitro and In vivo Evidence - Seo, Hee; Seong, Hyunbin; Kim, Ga Yun; Jo, Yu Mi; Cheon, Seong Won; Song, Youngju; Ryu, Byung Hee; Kang, Hee; Han, Nam Soo (Frontiers in Microbiology, 2021)
The use of probiotic starters can improve the sensory and health-promoting properties of fermented foods. In this study, we developed an anti-inflammatory probiotic starter, Limosilactobacillus reuteri EFEL6901, for use in kimchi fermentation. The EFEL6901 strain was safe for use in foods and was stable under human gastrointestinal conditions. In in vitro experiments, EFEL6901 cells adhered well to colonic epithelial cells and decreased nitric oxide production in lipopolysaccharide-induced macrophages. In in vivo experiments, oral administration of EFEL6901 to DSS-induced colitis mice models significantly alleviated the observed colitis symptoms, prevented body weight loss, lowered the disease activity index score, and prevented colon length shortening. Analysis of these results indicated that EFEL6901 played a probiotic role by preventing the overproduction of pro-inflammatory cytokines, improving gut barrier function, and up-regulating the concentrations of short-chain fatty acids. In addition, EFEL6901 made a fast growth in a simulated kimchi juice and it synthesized similar amounts of metabolites in nabak-kimchi comparable to a commercial kimchi. This study demonstrates that EFEL6901 can be used as a suitable kimchi starter to promote gut health and product quality.